The new criminal justice thinking - Dolovich, Sharon; Natapoff, Alexandra (New York : New York University Press, 2017)
This work offers a wide range of theoretical tools for conceptualizing the criminal justice system in general and this historical moment in particular, in which mass incarceration, the War on Drugs, police practices, the treatment of juveniles and the mentally ill, glaring racial disparity, and the death penalty (among other aspects) are all facing challenge. Each of the 14 original essays in this volume dismantles and reframes core debates over U.S. criminal justice.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 31, 2017).
Keywords: Criminal justice, Administration of -- United States; True Crime; Social services & welfare, criminology